Disruption of Transitional Stages in 24-h Blood Pressure Recording in Renal Transplant Recipients - Katz, Marcelo E.; Margulis, Fernando; Schiavelli, Ruben O.; Arias, Pablo; Head, Geoffrey A.; Golombek, Diego A. (Frontiers in Neurology, 2012)
Patients with kidney replacement exhibit disrupted circadian rhythms. Most studies measuring blood pressure use the dipper/non-dipper classification, which does not consider analysis of transitional stages between low and high blood pressure, confidence intervals nor shifts in the time of peak, while assuming subjective onsets of night and day phases. In order to better understand the nature of daily variation of blood pressure in these patients, we analyzed 24 h recordings from 41 renal transplant recipients using the non-symmetrical double-logistic fitting assessment which does not assume abruptness nor symmetry in ascending and descending stages of the blood pressure profile, and a cosine best-fitting regression method (Cosinor). Compared with matched controls, double-logistic fitting showed that the times for most transitional stages (ascending systolic and descending systolic, diastolic, and mean arterial pressure) had a wider distribution along the 24-h. The proportion of individuals without daily blood pressure rhythm in the transplanted group was larger only for systolic arterial pressure, and the amplitude showed no significant difference. Furthermore, the transplant recipient group had a less pronounced slope in descending systolic and ascending mean blood pressure. Cosinor analysis confirmed this phase-related changes, showing a wider distribution of times of peak (acrophases). We conclude that daily disruptions in renal transplant recipients can be explained not necessarily by an absence in diurnal variation, but also by changes in waveform-related parameters of the rhythm, and that alterations in the phase of the rhythm are the most consistent finding in these patients.